Biomineralization of hydroxyethyl cellulose/sodium alginate impregnated with cellulose nanocrystals by using surface modification technique - Etdal, Bakhiet (2021)
Bone tissue engineering utilizes scaffolds fabricated from various biopolymeric materials to obtain a specific topography prior to seeding with specified cells and implantation into an injured body. The aim of this research is to synthesize biopolymeric materials from hydroxylethylcellulose (HEC) (5 wt%) blended with sodium alginate (SA)(10 wt%) at 1:1 ratio and incorporated with cellulose nanocrystals (CNC) (11 w/v%). The scaffolds was fabricated using the freeze-drying technique. For the mineralization process, these HEC/SA and HEC/SA/CNC scaffolds were treated with simulated body fluid (SBF) by immersion technique through the depositing of calcium phosphate on the scaffold’s surfaces. The behavior of scaffolds such as chemical structures and thermal properties were characterized by using FESEM, EDX, ATR-FTIR, and UTM. In-vitro biocompatibility of the scaffolds was investigated by culturing human fetal osteoblast (hFOB) cells on these scaffolds. The SEM images displayed interconnected porous structures with diameters ranging from 40 to 400 μm and porosity percentages ranging from 75 ± 5% to 90.5 ± 5 %. The high swelling ratio of HEC/SA untreated with SBF scaffold was ascribed to the strong hydrogen bonding and Van der Waals interactions between polymer chains. After 7 days of incubation, the scaffolds began to disintegrate, which leads to the increase in weight loss (simultaneously up to ~60%). ATR-FTIR results exhibit possible interactions between hydroxyl groups of HEC, SA and CNC in the blends suggests there is chemical interaction between scaffolds. The TGA results showed four different regions of mass losses, represents the degradation temperature and water disposal, side - chain bond breaking, pyrolysis of SA and dehydroxylation behavior of calcium phosphate, respectively. The cell-scaffolds interaction demonstrated that hFOB cells differentiated and spread well on the scaffolds with better cell proliferation and attachment on HEC/SA/CNC treated with SBF porous scaffolds. Since these biocompatible and biodegradable scaffolds showed promising results, these scaffolds could be adopted for the design of next-generation tissue-engineered bone grafts.